Preface for the Special Issue of the fifth International Conference of Computer Science and Artificial Intelligence’24, ICCSAI’24: Integrating Artificial Intelligence with Computer Science for Intricate Systems, Cross-Disciplinary Insights, and Advanced solutions - BANOUAR, Oumayma; EL HADAJ, Salah; GUARMAH, Mahdi (Statistics, Optimization & Information Computing, 2026)
The main contributions of [Stat. Optim. Inf. Comput. Vol.15, No.2 (2026): ICCSAI’24], consisting of fifteen papers selected and revised from the fifth International Conference of Computer Science and Artificial Intelligence’24, are highlighted.